Collective Choice and Social Welfare An Expanded Edition - Amartya Sen (London Penguin Books, 2016)
Originally published in 1970, this classic study has been recognized for its groundbreaking role in integrating economics and ethics, and for its influence in opening up new areas of research in social choice, including aggregative assessment. It has also had a large influence on international organizations, including the United Nations, notably in its work on human development. The book showed that the ?impossibility theorems? in social choice theory―led by the pioneering work of Kenneth Arrow―do not negate the possibility of reasoned and democratic social choice.
Includes Index and Bibliography
Keywords: Welfare economics; Social choice